Novel Phosphorylation-State Specific Antibodies Reveal Differential Deposition of Ser26 Phosphorylated Aβ Species in a Mouse Model of Alzheimer’s Disease - Kumar, Sathish; Kapadia, Akshay; Theil, Sandra; Joshi, Pranav; Riffel, Florian; Heneka, Michael T.; Walter, Jochen (Frontiers in Molecular Neuroscience, 2021)
Aggregation and deposition of amyloid-β (Aβ) peptides in extracellular plaques and in the cerebral vasculature are prominent neuropathological features of Alzheimer’s disease (AD), and are closely associated with the pathogenesis of AD. Amyloid plaques in the brains of most AD patients and transgenic mouse models exhibit heterogeneity in the composition of Aβ deposits, due to the occurrence of elongated, truncated and post-translationally modified Aβ peptides. Importantly, these different Aβ variants are also associated with the clinical disease progression, and are considered to mark sequential phases of plaque and cerebral amyloid angiopathy (CAA) maturation at distinct stages of AD. We recently showed that Aβ phosphorylated at serine residue 26 (pSer26Aβ) has peculiar characteristics in aggregation, deposition and neurotoxicity. In the current study, we developed and thoroughly validated novel monoclonal and polyclonal antibodies that recognize Aβ depending on the phosphorylation-state of Ser26. Our results demonstrate that selected phosphorylation state-specific antibodies were able to recognize Ser26 phosphorylated and non-phosphorylated Aβ with high specificity in enzyme-linked immunosorbent assay (ELISA) and Western Blotting (WB) assays. Furthermore, immunofluorescence analyses with these antibodies demonstrated the occurrence of pSer26Aβ in transgenic mouse brains that show differential deposition as compared to non-phosphorylated Aβ (npAβ) or other modified Aβ species. Notably, pSer26Aβ species were faintly detected in extracellular Aβ plaques, but was most prominently found intraneuronally and in cerebral blood vessels. In conclusion, we developed new antibodies to specifically differentiate Aβ peptides depending on the phosphorylation state of Ser26, which are applicable in ELISA, WB and immunofluorescence staining of mouse brain tissues. These site- and phosphorylation state-specific Aβ antibodies represent novel tools to examine phosphorylated Aβ species to further understand and dissect the complexity in the age-related and spatio-temporal deposition of different Aβ variants in transgenic mouse models and human AD brains.